What it takes for women to reach the corporate boardrooms in Malaysia - Ku Ismail, Ku Nor Izah; Abd Rahman, Intan Maiza; Mustapa, Ifa Rizad; Abdullah, Shamsul Nahar (Virtus interpress, 2017)
This study seeks to understand how and why women were selected as board members, and reasons for women to accept board appointments.We conduct a questionnaire survey on women who sit on the boards of companies in Malaysia.We provide evidence that education, expertise and leadership qualities are necessary for women to reach the boardrooms.Their willingness to contribute to and share their expertise with a company are the main factors for women to accept the appointment as a director.The women feel that gender is not important in becoming a director compared to one’s capability.A majority of them were recommended by the CEO or other board members to become directors.The outcome of this study complements and strengthens the efforts made by the Malaysian government to achieve the 30 percent target.It is also very beneficial to women who aspire to become corporate directors.